2013
DOI: 10.1002/ptr.4973
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Primary Chronic Glomerulonephritis with Rehmannia Glutinosa Acteosides in Combination with the Angiotensin Receptor Blocker Irbesartan: A Randomized Controlled Trial

Abstract: This study aims to assess the efficacy and safety of Rehmannia glutinosa acteosides used in combination with the angiotensin receptor blocker irbesartan to treat primary chronic glomerulonephritis. A total of 479 patients diagnosed with primary chronic glomerulonephritis were recruited from outpatient clinics and were randomly assigned to the treatment group (Rehmannia glutinosa acteosides, two 200-mg capsules, bid; and irbesartan, one 150-mg tablet, qd) or the control group (irbesartan, one 150-mg tablet, qd)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Hong et al. have proved that urinary protein levels were more effectively controlled in patients with chronic nephritis treated with Rehmannia glutinosa acteoside and irbesartan compared with irbesartan [ 13 ], but the effect of acteoside in IgAN is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al. have proved that urinary protein levels were more effectively controlled in patients with chronic nephritis treated with Rehmannia glutinosa acteoside and irbesartan compared with irbesartan [ 13 ], but the effect of acteoside in IgAN is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A 6-year randomized trial in IgA nephritis showed that high dose losartan (200 mg/day) was more efficacious in reducing proteinuria as well as preserving renal function when compared with normal dose losartan (100 mg/day) and enalapril (20 mg/day; Woo et al, 2008). In a randomized controlled trial conducted by Qiu et al (2014), irbesartan significantly reduced proteinuria in 479 patients with primary chronic glomerulonephritis. However, its combination with Rehmannia glutinosa acteosides yielded a greater reduction in proteinuria.…”
Section: Arbs In the Treatment Of Nephritismentioning
confidence: 99%
“…The dry root of Rehmannia glutinosa Libosch (Scrophulariaceae) has been widely used as a traditional Chinese herbal medicine for neuroprotection, immune enhancement, hepatoprotection, prevention of bone loss, and treatment of primary chronic glomerulonephritis, learning and memory impairment, and anti-depression [24][25][26][27][28][29]. Catalpol, a major bioactive compound enriched by the dried root of R. glutinosa with the chemical structure previously shown [30], has been found to demonstrate broad and diverse bioactivities including neuroprotection, ameliorating cognition deficits and diabetic encephalopathy, potentially attenuating inflammation-related neurodegenerative diseases, protection against cerebral and cardiac ischemia/reperfusion injury, hepatoprotection, and radioprotection [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%